Hypermethylation of the TPEF/HPP1 Gene in Primary, Metastatic Colorectal Cancers - Matthias P.A. Ebert; Suzanne H. Mooney; Lori Tonnes-Priddy; Joe Lograsso; Juliane Hoffmann; Jie Chent; Christoph Rocken; Hans-Ulrich Schulz; Peter Malfertheiner; Catherine Lofton-Day (Neoplasia: An International Journal for Oncology Research, 2005)
The role of promoter methylation in the process of cancer cell metastasis has not yet been studied. Recently, methylation of the TPEF (transmembrane protein containing epidermal growth factor, follistatin domain) gene was reported in human colon, gastric, bladder cancer cells. Using the Methylight assay, TPEF/HPP1 gene methylation was assessed in primary colorectal cancers (n = 47), matched normal colon mucosa, as well as in the liver metastasis of 24 patients with colorectal cancer, compared to the methylation status of the TIMP-3, APC, DAPK, caveolin-2, p16 genes. TPEF was frequently methylated in primary colorectal cancers (36 of 47) compared to the normal colon mucosa (1 of 21) (P < .0001). Interestingly, promoter methylation was significantly more frequent in proximal nonrectal cancers (P < .05). Furthermore, a high degree of methylation of the TPEF gene was also observed in liver metastasis. (19 of 24). In summary, we observed frequent TPEF methylation in primary colorectal cancers, liver metastases, indicating that epigenetic alterations are not only present in the early phases of carcinogenesis, but are also common in metastatic lesions. The high frequency of TPEF methylation in this series of colorectal cancers underscores the importance of epigenetic changes as targets for the development of molecular tests for cancer diagnosis.